An assessment of the available alternatives for fusion relevant neutron sources. (13th July 2018) - Knaster, J.
Abstract: The discovery of void swelling in neutron-irradiated stainless steels by Cawthorne and Fulton in 1966 showed that radiation effects would seriously affect the lifetime of fission reactors. A few years later, in the early 1970s, serious damage levels were observed in core components of the first commercial fission reactors that had been in operation for one decade. Driven by the harder neutron spectrum, the fusion community was impelled to explore the technical possibilities to make available a fusion relevant neutron source to anticipate the difficulties faced by the fission reactors community and ensure the long-term operation of a fusion reactor. In 1976, the conclusions of the first review published announced the assets and drawbacks of the different possibilities, which today despite the four decades passed and the sound technological advancements, continue being basically the same. A suitable neutron spectrum can be theoretically obtained both from plasma-based or accelerators based facilities with either gas, liquid or solids targets. Needed facilities performances, available irradiation volumes that the concept allow and cost are at stake. In the past, the cost of the most promising facility based on stripping the neutron from a deuteron on a lithium target was misleadingly peered with that of a fusion reactor. A tokamak with sufficient volume to irradiate equipment under fusion relevant conditions will be likely available in the future once commercial fusion reactors have become a reality; unfortunately, this concept does not match the needs timely, and is unrealistic w.r.t. its costs nowadays with worldwide efforts prioritizing ITER. In this article, we will focus on the technical aspects and assess the present maturity of different existing possibilities based on nowadays technologies to count with neutrons at a suitable flux and spectrum to characterize and qualify fusion materials to be timely ready with our world fusion roadmaps.